2013
DOI: 10.1377/hlthaff.2012.1010
|View full text |Cite
|
Sign up to set email alerts
|

Physicians May Need More Than Higher Reimbursements To Expand Medicaid Participation: Findings From Washington State

Abstract: The expansion of insurance coverage under the Affordable Care Act is expected to put considerable pressure on the capacity of the primary care workforce to meet the needs of the Medicaid population beginning in 2014. The results from a 2011 survey and focus-group sessions with Washington State primary care physicians suggest that doctors welcome planned increases in Medicaid reimbursement rates. However, the data also show that other approaches could be even more effective in increasing physicians' willingness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 7 publications
1
46
0
Order By: Relevance
“…6,14,19,21 Poor access is postulated to result in Medicaid patients presenting with long-standing pathology that has progressed further than it would in patients with private insurance. 10 There are many reasons that contribute to the poorer access to specialty care with Medicaid insurance, such as Medicaid’s low reimbursement, 7,20,23 Medicaid patients’ increased complexity, 10 Medicaid’s onerous insurance paperwork and extended payment periods, 11,18 and Medicaid patients’ difficulty obtaining prompt appointments with their PCPs. 8 Given these challenges, surgeons may view patients who have taken the initiative to obtain a PCP referral as more amenable to treatment.…”
Section: Discussionmentioning
confidence: 99%
“…6,14,19,21 Poor access is postulated to result in Medicaid patients presenting with long-standing pathology that has progressed further than it would in patients with private insurance. 10 There are many reasons that contribute to the poorer access to specialty care with Medicaid insurance, such as Medicaid’s low reimbursement, 7,20,23 Medicaid patients’ increased complexity, 10 Medicaid’s onerous insurance paperwork and extended payment periods, 11,18 and Medicaid patients’ difficulty obtaining prompt appointments with their PCPs. 8 Given these challenges, surgeons may view patients who have taken the initiative to obtain a PCP referral as more amenable to treatment.…”
Section: Discussionmentioning
confidence: 99%
“…42 Financial compensation is not the only issue. 43,44 Among physicians who decline to accept Medicaid patients or limit the number they will treat, 76% cite onerous paperwork requirements and 60% cite the clinical complexity of patients enrolled in Medicaid. 45 Although reducing paperwork burdens and offering more support for those caring for patients with complex medical conditions could produce increased provider participation in the program, some observers have suggested that an ethic of professionalism alone should lead all physicians to treat at least some Medicaid patients.…”
Section: Ac a E Xpansion And Future Challengesmentioning
confidence: 99%
“…6 Previous studies have demonstrated that Medicaid patients come from more socioeconomically disadvantaged backgrounds, are more likely to be noncompliant with medical instructions, and pose increased regulatory hurdles for processing reimbursements. 3,6,11 A recent study analyzed the influence of patient insurance status on access to total knee and hips arthroplasty procedures. 9 To our knowledge, no study has examined patient access to foot and ankle care, including total ankle arthroplasty (TAA).…”
Section: Introductionmentioning
confidence: 99%